Analysis of 12 GWAS-Linked Loci With Parkinson’s Disease in the Chinese Han Population - Fan, Liyuan; Shi, Changhe; Hu, Xinchao; Zhang, Zhongxian; Zheng, Huimin; Luo, Haiyang; Fan, Yu; Zhang, Shuo; Hu, Zhengwei; Yang, Jing; Mao, Chengyuan; Xu, Yuming (Frontiers in Neurology, 2021)
A recent large-scale European-originated genome-wide association study identified 38 novel independent risk signals in 37 loci for Parkinson’s disease (PD). However, whether these new loci are associated with PD in Asian populations remain elusive. The present study aimed to explore the relationship between 12 most relevant loci with larger absolute values of these new risk loci and PD in the Chinese Han population. We performed a case-control study including 527 PD patients and 435 healthy controls. In allele model, it was found that rs10748818/GBF1 was associated with PD in the Chinese Han population ( p =0.035, odd ratio [OR] 1.221, 95% confidence interval [CI] 1.014-1.472). After further age-stratified analysis, rs11950533/C5orf24 and rs76949143/GS1-124K5·11 were shown related to early-onset PD (p =0.034) and late-onset PD (p =0.042) in genotype model, respectively. In contrast, no significant association with PD was found in the remaining 9 loci (rs34025766/LCORL, rs55961674/KPNA1, rs61169879/BRIP1, rs666463/DNAH17, rs75859381/RPS12, rs76116224/KCNS3, rs77351827/CRLS1, rs7938782/RNF141, rs850738/FAM171A2) either in allele or genotype frequencies. Our study revealed that the variants of rs10748818/GBF1 was associated with PD in allele model; after age-stratified analysis, rs11950533/C5orf24 and rs76949143/GS1-124K5·11 were associated with early-onset PD and late-onset PD in Chinese Han population, respectively.